Pendekatan Preferensi sebagai Umpan Balik pada Calon Varietas Unggul Baru yang Berdaya Saing - Imam Sutrisno; Titik Sundari; Febria Cahya Indriani; Nila Prasetiaswati; Joko Restuono (Proceedings Series on Physical & Formal Sciences, 2022)
Purple sweet potato farming in Banyuwangi as a mainstay commodity to support farmers' income. The local variety TW became the preferred local variety, but farmers began to complain about the decline in productivity. These problems need an effort to improve the use of local varieties in the use of superior varieties in restoring the productivity level of purple sweet potato to its original state. Thus, it is necessary to dame plots of prospective superior varieties to obtain farmer's assessment and preferences before purple sweet potato clones are released into varieties that have legality as VUB. The results showed that farmers and traders liked the skin and tuber shape of MSU 1001-15 and MSU 1002-07 clones. The reasons farmers chose the two clones were because: 1) they had a bright color and rather thick skin, 2) the shape of the large tubers was not too round and elongated, and the yield was high. The value of purple sweet potato farming in Banyuwangi is economically feasible in terms of marketing and income value which has a significant advantage.